Analisis Kemampuan Berpikir Kritis Matematis dan Motivasi Belajar Siswa pada Materi Barisan dan Deret Aritmatika - Handayani, Netti; Mulyono, Dodik; Charli, Leo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze students' mathematical critical thinking ability and learning motivation on the topic of Arithmetic Sequences and Series among grade X students at SMA Negeri Rupit. The research employed a descriptive qualitative method supported by quantitative data. The participants were 36 students consisting of 16 males and 20 females. Data were collected through a mathematical critical thinking test, learning motivation questionnaire, semi-structured interviews, and classroom observations. The results revealed that students' mathematical critical thinking ability was in the moderate category with an average score of 60.18%. Learning motivation was categorized as low with an average of 55.40%. The conclusion is there was a positive relationship between critical thinking ability and learning motivation. It is recommended that mathematics learning should implement Problem-Based Learning (PBL) and Contextual Teaching and Learning (CTL) models combined with STEM-based media to simultaneously enhance students' critical thinking skills and learning motivation. Keywords: Arithmetic Sequences and Series, Learning Motivation, Mathematical Critical Thinking Ability